2018
DOI: 10.1136/ejhpharm-2017-001411
|View full text |Cite
|
Sign up to set email alerts
|

Improvement on prescribing appropriateness after implementing an interdisciplinary pharmacotherapy quality programme in a long-term care hospital

Abstract: ObjectivesTo determine the prevalence of inappropriate prescribing in elderly patients with polypharmacy admitted to a long-term care hospital (LTCH) and to evaluate the impact of an interdisciplinary pharmacotherapy quality programme on improvement of prescribing appropriateness.MethodsAn interventional, longitudinal, prospective study was conducted in a Spanish LTCH (October 2013 to July 2014) including 162 elderly (≥70 years) patients with polypharmacy (≥5 medications). Pharmacists conducted the pharmacothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
1
9
0
2
Order By: Relevance
“…The use of tools proved to be valuable in a long-term care hospital resulting in a 31% improvement in prescribing appropriateness and led to deprescribing. 42 Although the study was conducted in a different care setting, it is reasonable to expect positive results to be translated amongst patients residing in community healthcare. Available tools and aids warrant a critical approach when applying to different settings and patients and should not replace a personalised approach to every deprescribing case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of tools proved to be valuable in a long-term care hospital resulting in a 31% improvement in prescribing appropriateness and led to deprescribing. 42 Although the study was conducted in a different care setting, it is reasonable to expect positive results to be translated amongst patients residing in community healthcare. Available tools and aids warrant a critical approach when applying to different settings and patients and should not replace a personalised approach to every deprescribing case.…”
Section: Discussionmentioning
confidence: 99%
“…Most tools were developed for elderly patients with polypharmacy and polymorbidity and for inpatient settings. The use of tools proved to be valuable in a long‐term care hospital resulting in a 31% improvement in prescribing appropriateness and led to deprescribing 42 . Although the study was conducted in a different care setting, it is reasonable to expect positive results to be translated amongst patients residing in community healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…This is traditionally done by medication history taking, medication reconciliation (MedRec), medication review (MedRev) and medication counselling, but requires working directly with patients, physicians and other healthcare professionals and includes communication to ensure that medications are correctly used. [1][2][3][4][5][6] The employment of clinical pharmacists in hospitals has shown improvement in many aspects of medicines safety, for example, prescribing appropriateness with reduction of potentially inappropriate medications from 17.0% to 12.2%, reduction of potentially prescribing omissions from 2.2% to 0.7% 7 and increased appropriate use of antimicrobials with almost 80% acceptance rate of pharmacist recommendations. 8 Seven of twelve trials in a review by Kaboli et al reported on reduction of DRPs and medication errors.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacist participation has been shown to improve the quality of medication reconciliation in a number of studies [10,16–21] . Pharmacists can identify more nonprescription and herbal medications than physicians or nurses using the medication reconciliation approach when patients are admitted to hospital [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on medication reconciliation by pharmacists were shown to be effective or beneficial. However, the overall results of medication reviews or medication reconciliation remain controversial due to different study designs, research settings, consensus of the pharmaceutical intervention, institutional settings, and the ages of the studied populations [10,18–21] . The majority of such studies are undertaken in a hospital setting.…”
Section: Introductionmentioning
confidence: 99%